Evaluation of processing methods and microbial analysis of Pito (an African indigenous beer), at selected production sites in Ghana - Zaukuu, John-Lewis Zinia (2016)
A thesis submitted to the Department of Food Science and Technology, College of Science in partial fulfilment of the requirements for the degree of Masters of Science in Food Science and Technology.